Towards a New Approach to Match Analysis: Understanding football players’ synchronization using tactical metrics - Clemente, Filipe Manuel Batista (2015)
Tese de doutoramento em Ciências do Desporto, ramo de Treino Desportivo, apresentada à Faculdade de Ciências do Desporto e Educação Física da Universidade de Coimbra